Oral protein‐based supplements for people with chronic kidney disease requiring dialysis - Mah, Jia Yee (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: This review aims to look at the benefits and harms of using oral protein‐based supplements to improve the nutritional state of patients with CKD requiring dialysis.